Fear of Displacement: Disruption in Place Attachment in Don DeLillo’s White Noise - FAZLZADEH, Naghmeh; Motallebzadeh, Nasser; Dashtpeyma, Nasser (Anafora, 2023)
Spatial criticism is an attempt to study environmental literature to demonstrate relationships between physical spaces and identity. Place attachment is a concept of environmental psychology that deals with the emotional bonds between individuals and the environment in which they feel secure. It is through the concepts of place identity and sense of place that scholars bring to the fore the concept of place attachment. Extending this thinking, the present paper seeks to propose place attachment and fear of disruption in attachment as the main reason for Jack Gladney’s fear of death. The protagonist of Don DeLillo’s White Noise (1985) has developed a strong sense of place, identity and belonging to the space of town, supermarket, and his house. Jack’s obsession with the cyberspace of TV and its psychic data is also examined in this paper. The aim of this paper is thus to study the formulation of the sense of place in Gladney. His place attachment and the fear of disruption are also studied at the crossroad of spatial criticism and trauma theory. The paper concludes by demonstrating how the fear of displacement causes haunting fear and anxiety in Jack Gladney.